Pulmonary adenocarcinoma in two alpacas (Vicugna pacos). Issue 4 (21st December 2020) - Moore, S Jo; Wessels, Mark; McFadzean, Harriet; Bell, Fraser; Treharne, Zoe V
Abstract : We describe here two cases of pulmonary neoplasia in alpacas: case 1 was a 19-year-old female huacaya alpaca that was submitted to investigate sudden death with possible previous weight loss. Gross and histological examination revealed changes consistent with primary lepidic-type pulmonary adenocarcinoma (previously bronchioalveolar carcinoma) with metastases to the thorax and abdomen. Case 2 was a six-year-old male castrated Suri alpaca with a 3-week history of weight loss and inappetance that was euthanased following a short period of recumbency and respiratory signs. Gross and histological features in this case were consistent with a diagnosis of metastatic adenocarcinoma affecting the lungs and lymph nodes. Masses from both alpacas were further characterised using immunohistochemistry for thyroid transcription factor 1 (TTF-1), pan cytokeratin AE1/AE3 and vimentin. We show that histological subtype and TTF-1 and AE1/AE3 immunoreactivity can be used to differentiate primary and metastatic pulmonary adenocarcinomas in the lungs of alpacas.